Caisson construction / Amirul Syafiq Zainal Abidin - Zainal Abidin, Amirul Syafiq (Universiti Teknologi MARA, Perak, 2015)
Excavated caisson is among the conventional method which slightly use machinery and more on labour. Excavated caisson is familiar foundation used in this country and there was many types of caisson use in this world depending on the soil factor to be considered. This report explained the process during the construction of excavated caisson and other test involved in order to ensure the granite is pass the engineering requirements before start to install the reinforcement and concrete. This report will show the process and method to construct the excavated caisson. So the construction of excavated caisson is the most crucial part of the structure because to receive such massive load from live and dead load of the structure to give strength to the foundation to support the loads.